Identification of Factors Influencing the Quality of Life in European Union Countries Evaluated by Principal Component Analysis - Ivanová, Monika; Klamár, Radoslav; Fecková Škrabuľáková, Erika (Geographica Pannonica, 2022)
In the paper we evaluate the quality of life in European Union countries. The introductory database is made up of 19 variables which, in our view, appropriately capture numerous spheres of human life. The reference date for this data, taken from the Eurostat database is April 10, 2021. The Principal Component Analysis that we have used in this paper is not rare in the conditions of multivariate statistics, however, when evaluating the quality of life, it is not much used. Many authors dealing with the topic take advantage of the traditional questionnaire survey and the points-based approach when analysing data. Our objective was to demonstrate that the Principal Component Analysis can be used in evaluating quality of life, especially if it is necessary to evaluate a significant number of variables and select factors with the highest impact. Apart from the main objective - the identification of factors most impacting the quality of life in European Union countries, we also focused on the comparison of countries as per particular main factors and searched for what caused differences between them. Quality of life is also reflected in the subjective perception of responders’ happiness. We were concerned to know whether the evaluated data would indicate that the feeling of happiness increases along with prosperity, or does not depend on growing prosperity at a certain stage.